2019
DOI: 10.1002/icd.2131
|View full text |Cite
|
Sign up to set email alerts
|

Shy children's understanding of irony: Better comprehension does not always mean better socioemotional functioning

Abstract: Childhood shyness is a risk factor for negative socioemotional outcomes including loneliness and depression. Childhood shyness has also been found to relate to various aspects of pragmatic language. For instance, shyer children rate ironic criticisms (i.e., where a speaker's intended meaning is the opposite of what is literally said) as meaner than do less shy children. This study examined whether relations between shyness and socioemotional functioning (i.e., loneliness, depression, and peer experiences) in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 92 publications
(147 reference statements)
0
11
0
Order By: Relevance
“…Relatedly, given that a large proportion of variance in children's pragmatic abilities was attributable to demographic factors, in future work it may prove insightful to explore the interplay of shyness and EF in different age and/or gender groups. Regarding the latter, for example, other studies have shown that shyness has a more negative impact on social‐emotional functioning in boys versus girls (Coplan et al., 2007) and that certain language skills (e.g., irony comprehension) differentially affect these relations across genders (Mewhort‐Buist & Nilsen, 2019). Last, our findings must be interpreted within the context of a cross‐sectional research design, which precludes us from exploring directionality or commenting upon possible causal relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatedly, given that a large proportion of variance in children's pragmatic abilities was attributable to demographic factors, in future work it may prove insightful to explore the interplay of shyness and EF in different age and/or gender groups. Regarding the latter, for example, other studies have shown that shyness has a more negative impact on social‐emotional functioning in boys versus girls (Coplan et al., 2007) and that certain language skills (e.g., irony comprehension) differentially affect these relations across genders (Mewhort‐Buist & Nilsen, 2019). Last, our findings must be interpreted within the context of a cross‐sectional research design, which precludes us from exploring directionality or commenting upon possible causal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Last, our findings must be interpreted within the context of a cross‐sectional research design, which precludes us from exploring directionality or commenting upon possible causal relationships. Future work could employ longitudinal methodology to clarify how temperamental factors and cognitive processes uniquely and jointly support pragmatic development and to identify potential consequences for social‐emotional functioning—associations shown to be complex and sometimes contradictory based on extant work (e.g., Coplan & Weeks, 2009; Mewhort‐Buist & Nilsen, 2019; White et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, when using written materials, Pomareda et al (2019) found the muting function only for younger and not older adults. It is unclear if the muting function of sarcasm occurs in all circumstances (see Mewhort-Buist & Nilsen, 2019), and most studies on the Tinge Hypothesis included written materials (Pomareda et al, 2019;Thompson, Mackenzie, Leuthold & Filik, 2016;Schwoebel et al, 2000), leaving out prosody and nonverbal cues that contribute to the complexity of nonliteral language in everyday communication. The current experiment will test the Tinge Hypothesis using dynamic, audio-visual stimuli.…”
Section: Models On Nonliteral Language Processingmentioning
confidence: 99%
“…An alternative explanation of this finding is that children's close relationship with their teacher may help them better understand social conventions required for successful social interactions [70], since they may more easily acquire pragmatic skills from their teachers than those in negative relationships with their teachers. It was found that shy children with weaker pragmatic language skills are at higher risk for increased loneliness [70,71]. Shy children's emotional difficulty may develop when their teachers negatively respond to their shy behavior [70].…”
Section: Moderated Mediationmentioning
confidence: 99%